Motivation for Waqf in Millennials and Generation Z: Highlighting Religiosity, Literacy and Accessibility - Fiqran, Muh.; Mujahidin, Mujahidin; Noor Bakri, Adzan; Jasmin A. Abdulrahman, Atty. (Universitas Islam Negeri Raden Intan Lampung, 2024)
Indonesia has a huge potential for waqf. The magnitude of this potential is due to the majority Muslim population, especially millennials and generation Z. However, there are many factors that cause waqf to not be managed optimally by existing waqf institutions. This research discusses the motivation of millennials and generation Z in waqf through factor analysis of literacy, religiosity, and accessibility. The purpose of this study is to analyze whether literacy, religiosity, and accessibility have an influence on the motivation of the younger generation in waqf and see how much influence these factors have on the factors that motivate millennials and generation Z in waqf. The type of research used in this study is quantitative method. By collecting data using a questionnaire and involving 485 research respondents. After that, the data obtained was analyzed using the SEM analysis method supported by the Smart PLS application to determine the variables that have a significant effect on the motivation of millennials and generation Z in waqf. This research was conducted in South Sulawesi Province. The results of this study indicate that Religiosity and Accessibility have a significant and positive influence on the motivation of millennials and generation Z in waqf with each p-value of 0.000 which is smaller than 0.05 and a t-statistic value of 10.334 and 12.531, while Literacy does not show a significant effect with a p-value of 0.124 and a t-statistic of 1.537.